Leaching of heavy metals from fly ash - Dayang Norfadzila, Awang Johari (Universiti Malaysia Sarawak, UNIMAS, 2009)
Disposal of coal fly ash is a major issue due to its potential to cause surface and groundwater contamination. Stabilization is one of the effective methods of dealing with heavy metals in contaminated soil. In this study, the stabilization was evaluated using leaching tests. Fly ash samples was applied to the agricultural soil in the ratio of 1:9 in order to investigate the concentration of available metals (Cd, Zn, Ni, Mn, Cu, Cr and Fe) in leachates from 0 – 15 days of stabilization. The different mobilization media, namely deionized water and acidified water (deionized water acidified with nitric acid solution to pH = 4.0) was passed through to the soil-fly ash mixtures in the columns. Soil and fly ash samples were characterized for their physical and chemical properties as their properties greatly influenced the leaching potential. The heavy metals concentrations were analyzed by using Flame Atomic Absorption Spectrophotomter (FAAS). The results obtained from the leaching experiments showed that the addition of fly ash to agricultural soil had reduced the concentrations of available metals except for Cr. pH and electrical conductivity of leachates were analyzed and results found that pH increased while electrical conductivity decreased from 0 day to 15 days of contact time. Statistical analysis showed significant differences (P < 0.05) for particular metals between all treatments for almost at all contact time.